ERECTILE DYSFUNCTION IN MULTIPLE SCLEROSIS - Бурдин, Константин Александрович; Кызласов, Павел Сергеевич; Мартов, Алексей Георгиевич; Удалов, Юрий Дмитриевич; Помешкин, Евгений Владимирович; Забелин, Максим Васильевич (Medicine in Kuzbass, 2017)
The copulatory function is one of the criteria for determining a person's health. The pathogenesis mechanism of erection completely depends on the adequate functioning of the nervous system. Diseases, which lead to dysfunction of nerve impulse transmission, are the causes of erectile dysfunction. One such disease is multiple sclerosis. Given the rather early age of manifestation of the disease, erectile dysfunction can be one of the precursors of multiple sclerosis. The study of copulative dysfunction provides a unique opportunity to assess the work of the CNS in relation to sexual activity that helps to avoid psychological disorders. The article presents the analysis of the world data on the recommendations for diagnosis and treatment of erectile dysfunction in patients with multiple sclerosis. As advanced diagnostics, early detection in combination with effective medication allow these people to maintain a good quality and high standard of living.
Keywords: erectile dysfunction; multiple sclerosis; copulative function; inhibitors of PDE-5